Sub-Lethal Effects of Pesticides on the DNA of Soil Organisms as Early Ecotoxicological Biomarkers - Vischetti, Costantino; Casucci, Cristiano; De Bernardi, Arianna; Monaci, Elga; Tiano, Luca; Marcheggiani, Fabio; Ciani, Maurizio; Comitini, Francesca; Marini, Enrica; Taskin, Eren; Puglisi, Edoardo (Frontiers in Microbiology, 2020)
This review describes the researches performed in the last years to assess the impact of pesticides sub-lethal doses on soil microorganisms and non-target organisms in agricultural soil ecosystems. The overview was developed through the careful description and a critical analysis of three methodologies based on culture-independent approaches involving DNA extraction and sequencing (Denaturing Gradient Gel Electrophoresis, DGGE; Next Generation Sequencing, NGS) to characterize the microbial population and DNA damage assessment (Comet assay) to determine the effect on soil invertebrates. The examination of the related published articles showed a continuous improvement of the possibility to detect the detrimental effect of the pesticides on soil microorganisms and non-target organisms at a sub-lethal doses, i.e doses which have no lethal effect on the organisms. Considering the overall critical discussion on microbial soil monitoring in function of pesticide treatments, we can confirm the usefulness of PCR-DGGE as a screening technique to assess the genetic diversity of microbial communities. Nowadays, DGGE remains a preliminary technique to highlight rapidly the main differences in microbial community composition, able to give further information if coupled with culture-dependent microbiological approaches, while thorough assessements must be gained by high-throughput techniques such as NGS. Comet assay represents an elective technique for assessing genotoxicity in environmental biomonitoring, being mature after decades of implementation and widely used worldwide for its direct, simple and affordable implementation. Nonetheless, in order to promote consistency and reliability of results, regulatory bodies should provide guidelines on the optimal use of this tool strongly indicating the most reliable indicators of DNA damage. This review may help the European Regulation Authority in deriving new ecotoxicological endpoints to be included in the Registration Procedure of new pesticides.